„Sprzecznościowa" koncepcja literackości - Balcerzan, Edward (Przestrzenie Teorii, 2007)
Among determinants of literary character indicated by successive schools there is none which could be described as existing always and everywhere in the word art. What is worse, every one of them can be found also in the inartistic forms of expression. A substantial component (an excerpt) of a text cannot become the universal distinguishing feature of literature as the essence of literature is determined by specific intratextual and extratextual relations. These are "antinomic" relations, embracing everything which is to be found within the bounds of poetics of the composition - the "hard" textual fact as well as the expected result of reading, not only attributes of one particular level of the composition's structure, but also features of different layers. It causes tensions between phenotype and genotype, between text and non-verbal reality. These antinomies do not have equal power, they could be graduated, and they are placed in between extremes of solvability and unsolvability, agreement and destruction.